Narrativas digitais, autoria e currículo na formação de professores mediada pelas tecnologias: uma narrativa-tese - Rodrigues, Alessandra (2017)
Digital storytelling combine the tradition of storytelling with the contemporaneousness of information and communication technologies (ICT). When used in educational contexts, they can be spaces for the promotion of authorship and dialogue among the subjects of the curriculum, enhancing more meaningful, contextualized and critical-creative learning. Digital storytelling also allow association with the concept of narrative curriculum, although they have been little explored in the scope of scientific research. Considering this context of possible relations, this study aims to analyze the production and to advertising of digitals storytelling of learning (DSL) as a possibility for the construction of a narrative curriculum in teacher training and its influence: a) in the building of teacher authorships; B) in the approximation/appropriation/signification of the technology for pedagogical use. The research locus was a semi-presential discipline of the Graduate Program in Science Teaching of a Brazilian public university. In this course, the research subjects produced and presented their DSL during a semester. The methodological way of the research was made through the observation of the classes in the classroom, the monitoring the production and dissemination of the partial storytelling posted in a virtual environment and by holding focus groups with the subjects. The analysis is carried out from the intersection of the discourses of the subjects in the DSL and in the other enunciative contexts, having as guiding the three central themes of the study: authorship, narrative curriculum and ICT. Considering this movement, the research constitutes as a qualitative study of storytelling character, with ethnographic inspiration. The results of this research suggest that the construction of the narrative curriculum is associated with some elements (narrative learning and tertiary, narrative capital and experience) and has the storytelling way of thinking as structuring. This study also indicates that, as curricular elements, the DSL can be seen: a) as enhancing of the assumption of the author-function by the subjects; b) as instigators of the subjects' perception on the storytelling temporality of life and human constructions; c) as elements of critical-reflexive articulation between the prescriptive curricular contents and the subjects' knowledge, experiences and narrative capital; d) as spaces that promote storytelling learning and tertiary that contribute to the social future of the subjects, empowering them; e) as spaces of construction of narrative identities that allow subjects to define, appropriate and maintain the continuous storytelling of their own curricula; f) as promoters of autonomous processes of approximation, appropriation and resignification of the ICT for pedagogical use